2019
DOI: 10.3390/ijerph16111989
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Correlates of Motor Competence in Children—The Skilled Kids Study

Abstract: Environment, physical activity (PA) and motor development are tightly interwoven during childhood. We examined the associations of environmental factors with motor competence (MC) in children. Children (N = 945, 50.1% boys, age = 3–7 years, mean = 5.4 years) from 37 childcare centres in the Southern (n = 17), Central (n = 13) and Northern Finland (n = 7) participated. The environmental factors comprised the geographical location (Southern, Central and Northern Finland) and residential density (metropolitan are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 51 publications
3
78
1
4
Order By: Relevance
“…Therefore, whilst it appears that time outside benefits physical activity, the potential for specific motor skill benefits may be less clear. Although, a recent representative study in Finnish preschool aged children showed time outdoors was related to both object control and locomotor skills [30]. A limitation of the current study is that physical activity type was not assessed.…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, whilst it appears that time outside benefits physical activity, the potential for specific motor skill benefits may be less clear. Although, a recent representative study in Finnish preschool aged children showed time outdoors was related to both object control and locomotor skills [30]. A limitation of the current study is that physical activity type was not assessed.…”
Section: Discussionmentioning
confidence: 90%
“…So far, the studies that used aligned measurements of actual and perceived MC according to the specific MC domain have shown that the relationships were stronger in boys than in girls and in skills related to object control than to self-movement [22,65,66]. This study adds a new developmental view of the analysis of the association between actual and perceived MC: at the age of 10-13 the Chilean boys and girls are able to recognize their actual MC in object control at a moderate level.…”
Section: Discussionmentioning
confidence: 99%
“…Ten childcare centers (27%) declined to participate due to a lack of space, interest, time, or a low number of children. The aim of the Skilled Kids study and the recruitment process have been described in detail in previous studies [33,40,41]. For the recruited childcare centers, the respective directors first approved the participation, and the staff was informed about the study.…”
Section: Study Protocol and Participantsmentioning
confidence: 99%
“…Participation in organized sports was associated with better scores in both assessment tools, underlining the fact that during early childhood, motor development benefits from sports-related hobbies [38,41,58] related to LM skills [27,41], BS [41], and coordination [55]. Although participation in organized sports is mainly positively related to MC development, there may be differences between different environments [41] and countries [59]. Therefore, one should not forget the importance of outdoor play and everyday life choices [59] that help to accumulate more daily PA [60].…”
Section: Individual Correlates Of Motor Competencementioning
confidence: 99%